A qualitative examination of the impacts of financial stress on college students' well-being: Insights from a large, private institution. (May 2021) - Moore, Andrea; Nguyen, Annie; Rivas, Sabrina; Bany-Mohammed, Ayah; Majeika, Jarod; Martinez, Lauren
Objective: This qualitative research aims to provide deeper insight into college students' experiences by examining the impact of financial stress on their well-being. Methods: Four focus groups were conducted at a large, private, urban university in the United States over the course of 1 month, each lasting approximately 1 h. Facilitators used a structured moderator guide to maintain consistency. Four focus groups were conducted and a total of 30 students participated. Students were primarily Asian (66.7%) and White (30.0%), and a majority were female (86.7%). Student participants were 43.3% undergraduate and 56.6% graduate. Transcripts were analyzed in Atlas.ti 8 software using line-by-line open coding guided by the principles of qualitative content analysis. An inductive approach was utilized to code the data. Emergent categories and concepts were then organized hierarchically into themes and subthemes. Results: Two overarching themes emerged from the focus group analysis. In these students' perspectives, financial stress impedes their ability to succeed academically. Another major theme is the impact of finances on students' social lives. Students experiencing financial stress find it challenging to navigate relationships with wealthier peers, often leading to feelings of isolation and embarrassment. Conclusion: Given the reported negative impact on students' well-being, further research is needed to determine methods for mitigating financial stress.